Cuba straits - White, Randy Wayne (White, Randy Wayne. Doc Ford series, 2015)
"The remarkable new novel in the Doc Ford series by New York Times-bestselling author Randy Wayne White. Doc Ford's old friend, General Juan Garcia, has gone into the lucrative business of smuggling Cuban baseball players into the U.S. He is also feasting on profits made by buying historical treasures for pennies on the dollar. He prefers what dealers call HPC items-high-profile collectibles-but when he manages to obtain a collection of letters written by Fidel Castro between 1960-62 to a secret girlfriend, it's not a matter of money anymore. Garcia has stumbled way out of his depth. First Garcia disappears, and then the man to whom he sold the letters. When Doc Ford begins to investigate, he soon becomes convinced that those letters contain a secret that someone, or some powerful agency, cannot allow to be made public. A lot happened between Cuba and the United States from 1960-62. Many men died. A few more will hardly be noticed"--